Pengetahuan tahapan tumbuh kembang motorik anak sebagai upaya pencegahan keterlambatan tumbuh kembang - Ika Fitri Wulan Dhari; Andy Sirada; Fidyatul Nazhira (IKIP SILIWANGI, 2023)
Background: The thing that is very important in the stages of growth and development and becomes the basis for subsequent development is gross motor and fine motor skills. This is the basis for the achievement of aspects of children's growth and development, including the ability to speak and speak and socialize. Parents have an important role and have an impact on children's growth and development, so parents are expected to know the problems of early childhood motor physical development to avoid the occurrence of growth and further development disorders Purpose: provide knowledge about the importance of knowing the stages of children's motor growth and development Method: This activity was carried out through counseling to 29 Health cadres on coconut island on September 22, 2022, the level of knowledge of Health cadres was measured through a questionnaire consisting of 9 questions given before and after the implementation of counseling. Results: paired sample t test with results of p<0.05 or p = 0.0002 which means that there are significant results for increasing the knowledge of Health cadres before and after the distillation activity with an average value of knowledge level before counseling 6.2 (SD±0.86) and the average value after counseling 8.3 (SD±0.5). Conclusion: There is a significant increase in the level of knowledge of health cadres regarding the stages of motor growth and development in children.